A homology guide for Pacific salmon genus Oncorhynchus resolves patterns of ohnolog retention, resolution and local adaptation following the salmonid‐specific whole‐genome duplication event. Issue 4 (20th April 2023) - Dimos, Bradford; Phelps, Michael
Abstract: Salmonid fishes have emerged as a tractable model to study whole‐genome duplications (WGDs) as this group has undergone four rounds of WGDs. While most of the salmonid genome has returned to a diploid state, a significant proportion of genes are maintained as duplicates and are referred to as ohnologs. The fact that much of the modern salmonid gene repertoire is comprised of ohnologs, while other genes have returned to their singleton state creates complications for genetic studies by obscuring homology relationships. The difficulty this creates is particularly prominent in Pacific salmonids belonging to genus Oncorhynchus who are the focus of intense genetics‐based conservation and management efforts owing to the important ecological and cultural roles these fish play. To address this gap, we generated a homology guide for six species of Oncorhynchus with available genomes and used this guide to describe patterns of ohnolog retention and resolution. Overall, we find that ohnologs comprise approximately half of each species modern gene repertoires, which are functionally enriched for genes involved in DNA binding, while the less numerous singleton genes are heavily enriched in dosage‐sensitive processes such as mitochondrial metabolism. Additionally, by reanalyzing published expression data from locally adapted strains of O. mykiss, we show that numerous ohnologs exhibit adaptive expression profiles; however, ohnologs are not more likely to display adaptive signatures than either paralogs or singletons. Finally, we demonstrate the utility of our homology guide by investigating the evolutionary relationship among genes highlighted as playing a role in salmonid life‐history traits or gene editing targets. Abstract : We described how the salmonid‐specific whole‐genome duplication has influenced the gene repertoires of six species of Oncorhynchus . Overall, we found that gene function is a major driver of whether a gene will be retained as an ohnolog or it will revert to a singleton state, which in turn influences chromosomal synteny. We also produced a multi‐species homology guide which we hope will aid in the field of salmonid genetics.